SelfCare when working from home: easier but also more important - Krick, Annika; Arnold, Miriam; Felfe, Jörg (Frontiers in Organizational Psychology, 2024)
Introduction Telework brings opportunities (e.g., flexibility) but also potential risks for health (e.g., fewer boundaries, constant availability). SelfCare could be a relevant work-related resource to reduce these health risks when working from home. SelfCare is part of the Health-oriented Leadership model and describes how individuals prioritize their own health, are aware of signs of stress, and actively promote their own health. In this paper, we postulate that telework enables more SelfCare at home, e.g., due to higher flexibility and autonomy. As SelfCare at home can be used more flexibly, it is also conceivable that the effectiveness of SelfCare increases the more employees work from home. Additionally, for hybrid working employees, the question arises whether SelfCare at both work contexts is distinct and makes an independent contribution to health and whether they even reinforce each other. Methods Our hypotheses were tested in a longitudinal study with N = 727 employees from different industries. This study examined (1) the level of SelfCare on-site and at home (within- and between-person-effects), (2) the moderating effect of telework intensity on the effectiveness of SelfCare at home on health and performance indicators, and (3) direct and interacting effects of SelfCare at home and on-site for health. Results Between- and within-person-differences show that SelfCare is more prevalent when working from home. Furthermore, SelfCare at home is related to less strain and health complaints as well as more relaxation and performance for individuals with higher telework intensity. SelfCare at home and on-site independently predict strain and health complaints and interact with regard to strain. Discussion SelfCare appears to be more relevant with higher telework intensity and is thus an even more important health resource in the telework context. Organizations should provide continuing interventions and online tools to promote SelfCare among employees and leaders. Since little is known about the level and the effects of SelfCare in the telework context, these findings expand previous research on Health-oriented Leadership in the telework context.